Effect of Mixed Culture Lactic Acid Bacteria Fermentation and Autoclaving-Cooling Cycle on the Level of Resistant Starch Modified Purple Sweet Potato Flour (Ipomea batatas var Ayamurasaki - Setiarto, Raden Haryo Bimo; Widhyastuti, Nunuk (Warta Industri Hasil Pertanian, 2017)
This study aimed to analyze the influence of mixed culture of lactic acid bacteria fermentation and autoclaving-cooling cycle for resistant starch content of modified purple sweet potato flour. Purple sweet potato slices had been fermented with mixed cultures of lactic acid bacteria (Lactobacillus plantarum B-307:Leuconostoc mesenteroides SU-LS 67) (1:1) for 24 hours at 370C. Then, fermented purple sweet potato slices had been autoclaved (1210C, 15 min) and cooled (40C, 24 hours), treatment was done for one, two and three cycles. Furthermore, purple sweet potato slices was done dried (800C, 18 hours), ground and sieved (80 mesh) to obtain modified purple sweet potato flour. Combination autoclaving-cooling and fermentation can increase levels of resistant starch of modified purple sweet potato flour. The more number of autoclaving-cooling cycle had been applied can increase significantly the levels of resistant starch. Treatment fermentation with autoclaving-cooling 1 cycles (FAC-1S) produced the highest resistant starch content (11.26%) compared to other treatments and it increased levels of resistant starch by 5.34-fold compared to control (2.11%). Increased levels of resistant starch can contribute for decrease the digestibility of modified purple sweet potato flour.